Deriving and resolbing ambiguities in wieder-sentences - Egg, Markus (Proceedings of the Amsterdam Colloquium, 1999)
The frameworks of underspecification and of optimality theory can interact in the treatment of semantic ambiguity. Underspecification allows a compact yet comprehensive representation of an ambiguous expression, which is at the same time a suitable input for an optimality theory based resolution component that determines the preferred reading of the expression. Ambiguities of sentences with wieder 'again' are investigated to explore this claim.